Analysis of Financial Performance at Village-Owned Enterprises (BUMDES) X in Pangandaran for the 2018-2020 Period - Ratna Meisa Dai; Nurul Mardhiah Sitio; Ahmad Nur Fauzi (International Journal of Economics and Management Research, 2023)
This research aims to determine the Financial Performance of the BUMDes in Pangandaran Regency in the period 2018-2020. The data used in this research is secondary data sourced from the financial statements of BUMDes. Analysis of the data in this research using financial ratios to provide an overview of the financial condition of BUMDes. The results showed that the financial performance of the BUMDes for the 2018-2020 period in terms of the liquidity aspect showed very good and liquid results with an average ratio of 484%. The debt ratio shows very good results with an average ratio of 8%. NPM BUMDes showed very good results with an average ratio of 40%. Asset turnover gave poor results with an average of 0.8 times. Then cash turnover shows a decline every year with an average turnover of 2.43 times.